2013
DOI: 10.1262/jrd.2013-028
|View full text |Cite
|
Sign up to set email alerts
|

Embryo Sexing and Sex Chromosomal Chimerism Analysis by Loop-Mediated Isothermal Amplification in Cattle and Water Buffaloes

Abstract: In domestic animals of the family Bovidae, sex preselection of offspring has been demanded for convenience of milk/beef production and animal breeding. Development of the nonsurgical embryo transfer technique and sexing methods of preimplantation embryos made it possible. Sexing based on detection of Y chromosome-specific DNA sequences is considered the most reliable method to date. PCR enables amplification of a target sequence from a small number of blastomeres. However, it requires technical skill and is ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Furthermore, LAMP is less influenced by inhibitors present in complex samples than standard PCR, which is highly beneficial for clinical specimens such as blood components, sputum, feces, or body fluids ( Kaneko et al, 2007 ). LAMP assays have been widely applied to genetic diagnoses, the detection of epidemic bacteria ( Hara-Kudo et al, 2005 ; Song et al, 2005 ) and viruses ( Okafuji et al, 2005 ), fetal sex identification ( Hirayama et al, 2013 ), and parasite recognition ( Chen et al, 2011 ; Kong et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LAMP is less influenced by inhibitors present in complex samples than standard PCR, which is highly beneficial for clinical specimens such as blood components, sputum, feces, or body fluids ( Kaneko et al, 2007 ). LAMP assays have been widely applied to genetic diagnoses, the detection of epidemic bacteria ( Hara-Kudo et al, 2005 ; Song et al, 2005 ) and viruses ( Okafuji et al, 2005 ), fetal sex identification ( Hirayama et al, 2013 ), and parasite recognition ( Chen et al, 2011 ; Kong et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The LAMP assay does not require skilled operators or precise instruments, and is therefore practically applicable within point of care settings with poor resources. Since its introduction by Notomi et al ( 8 ) in 2000, it has been widely applied to a variety of fields, including clinical diagnosis, food safety, livestock breeding and determination of sex ( 18 , 19 ). This is largely due to its rapid and simple methodology.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that both genomic DNA a RNA can be isolated from single blastocysts, however due to the little amount of resultant DNA, we recommend improving the protocol of amplification of such minute amount of genomic DNA to give satisfactory results. Other researchers improved the DNA amplification used different kind of PCR protocol such as loop-mediated isothermal amplification (LAMP) [25], [26].
Fig. 1Representative image of gel electrophoresis showing validation of amplification of Y-specific segment by PCR.
…”
Section: Resultsmentioning
confidence: 99%